Investigation of high voltage discharge in service water; The 8th Korea-Russia International Symposium on Science and Technology (KORUS 2004), June 26 - July 3, 2004, Tomsk, Russia; Vol. 1 - Yushkov A. Yu. Anatoly Yurievich (2004, 2004)
Title screen